The Influence of Member Participation and Management Competence on Improving the Welfare of Women Farmer Groups in X Koto Singkarak District, Solok Regency - Hafidzatul Qurani, Mozia; Yeni, Afni; Nurhayati, Nurhayati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to identify and analyze the influence of member participation and management competence on improving the welfare of Women Farmers Groups in X Koto Singkarak District, Solok Regency. The background of this research is based on the low level of member participation and the limited competence of group management, as indicated by low attendance at routine group meetings, the failure to fulfill agreed responsibilities, and the lack of structured task distribution. The levels of member participation and management competence are considered not yet optimal; therefore, an empirical study is needed to examine their influence on improving group welfare. This study employed a quantitative research approach through questionnaire distribution. The findings reveal that member participation has a positive and significant effect on welfare improvement. Management competence also has a positive and significant effect on welfare improvement. Simultaneously, member participation and management competence have a positive and significant effect on improving the welfare of Women Farmers Groups in X Koto Singkarak District, Solok Regency.